Introduction: Early Catholic Orientalism and the Missionary Discovery of Asian Religions - Pomplun, Robert Trent; Rubiés, Joan-Pau; Županov, Ines G. (Journal of early modern history, 2020)
Abstract New encounters in America, Africa, and Asia facilitated the "discovery" of non-Biblical religious traditions that were distinct from the ancient paganism known to Christian humanists and antiquarians from classical sources and patristic literature. Although Hinduism, Buddhism, and Confucianism did not exist as concepts in the early modern period, the three articles in this special issue illustrate the learning process by which a number of influential and pioneering Catholic missionaries came to distinguish these various traditions from each other. We argue that they did not simply "invent" new religions arbitrarily: instead, on the basis of the very broad categories of true religion and idolatry, they engaged in some close interaction and "dialogue"-albeit usually polemical-with local religious elites and their writings, including Eastern Christians. In addition, in the case of the Jesuits in particular, we note that these various engagements were often connected events...